2009
DOI: 10.1136/vetrec.165.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analyses of respiratory gases made with the K4b2 portable and Quark laboratory analysers in horses

Abstract: Measurements of minute ventilation (VE) and expired oxygen and carbon dioxide fractions (FeO2 and FeCO2) were measured at rest and during exercise in seven warmblood horses performing two consecutive standardised incremental treadmill exercise tests at submaximal speed, using the portable K4b2 telemetric unit and the laboratory Quark metabolic cart in random order. Oxygen consumption (VO2) and carbon dioxide production (VCO2) were estimated using the Haldane equation. There were no significant differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…In addition, if we compare with the data given in other studies, at the speed required for winning endurance races (18 km/h), under treadmill conditions, with the K4B 2 gas‐exchange device, the extrapolated VO 2 seems lesser in Arabians than in other breeds. Indeed, 42 ml/min/kg bwt was reported in the Arabians of this study vs. 50.1 ml/min/kg bwt for Thoroughbred cross Warmblood horses (Leprêtre et al . 2009) and 70.8 for untrained saddle horses (Art et al .…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In addition, if we compare with the data given in other studies, at the speed required for winning endurance races (18 km/h), under treadmill conditions, with the K4B 2 gas‐exchange device, the extrapolated VO 2 seems lesser in Arabians than in other breeds. Indeed, 42 ml/min/kg bwt was reported in the Arabians of this study vs. 50.1 ml/min/kg bwt for Thoroughbred cross Warmblood horses (Leprêtre et al . 2009) and 70.8 for untrained saddle horses (Art et al .…”
Section: Discussionmentioning
confidence: 51%
“…Although the gas exchange device has already been validated during exercise (Art et al . 2006; Leprêtre et al . 2009), this study again confirmed that the respiratory mask was well accepted by the horses that performed the exercise test on the field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VO 2 is converted to EE from its caloric equivalent (Levine, 2005), and respiratory exchange ratio (RER) is calculated from VO 2 and VCO 2 , together giving information regarding substrate utilization during exercise. Although first attempts were made to develop portable devices for horses since 1974 (Hörnicke et al, 1974;Pagan et al, 1986;Hanak, 1987), it has only been in the last decade that the equine K4b 2 was validated Leprêtre et al, 2009). This system presents the advantage of measuring EE in genuine endurance conditions, including the extra load by the rider and tack or the condition of the ground surface (Lawrence, 2007).…”
Section: Introductionmentioning
confidence: 99%